Mummified Seed Cones of Pinus prehwangshanensis sp. nov. (Subgenus Pinus, Pinaceae) From the Upper Pleistocene of Guangdong, South China: Taxonomical Significance and Implication for Phytogeography and Ecology - Bazhenova, Natalia V.; Wu, Xin-Kai; Kodrul, Tatiana M.; Maslova, Natalia P.; Tekleva, Maria V.; Xu, Sheng-Lan; Jin, Jian-Hua (Frontiers in Ecology and Evolution, 2022)
Anatomical characters of Cenozoic pine seed cones are known mainly from North American fossils, while data on cone anatomy of Cenozoic species from Asia remain scarce. To date, only one seed cone of Pinus from the Miocene of eastern China has been studied using micro-computed tomography (micro-CT). A new fossil-species, Pinus prehwangshanensis sp. nov., of mummified seed cones from the upper Pleistocene of South China is described using a combination of scanning electron microscopy (SEM) and micro-CT. The new fossil-species combines a mosaic of seed cone morphological and anatomical characters observed in the group of closely related East Asian extant species of subgenus Pinus, section Pinus, subsection Pinus, comprising Pinus taiwanensis, Pinus hwangshanensis, Pinus luchuensis, Pinus thunbergii, and Pinus densiflora. The data obtained indicate that the characteristic anatomical features of this group were formed no later than the end of the Pleistocene. Based on the external seed cone morphology, the East Asian pine fossils confirm the existence of floristic exchange between continental Asia and the Japan archipelago prior to the formation of the Sea of Japan and later, in the middle Miocene to the late Pliocene, when the connection between the Japanese islands and Eurasian continent became re-established. Pollen grains associated with the new fossil-species are similar to those of some extant pine species related to P. thunbergii. A taxonomic and ecological analysis of the Pleistocene plant taxa from the Maoming Basin suggests that the regional climate was a humid subtropical monsoon with hot wet summers and cool dry winters, similar to the present-day climate of northeastern Vietnam.